Sir James Clark Ross and the Franklin Expedition - Cyriax, Richard J. (Polar Record, 1942)
No officers, apart from those who actually served in the Franklin expedition, were so closely connected with it, both before and after its departure, as Sir Edward Parry and Sir James Clark Ross. Parry, after his last Arctic expedition (1827), was consulted as a matter of course by the Admiralty on all Arctic problems; he assisted in organising the Franklin Expedition; and was one of the Admiralty's principal advisers during the search.